Suspicious minds: The psychological, physical and behavioral consequences of suspecting a partner's infidelity. (March 2021) - Weigel, Daniel J.; Shrout, M. Rosie
Guided by transactional stress theory, this study examined the psychological, physical, and behavioral consequences of the suspicion of a partner's infidelity. Survey data collected from 246 individuals revealed that suspecting a partner's infidelity was associated with greater reported suspicion-related distress, depression, physical health symptoms, and risky health behavior. Mediation and moderated mediation analyses revealed that the relationship between suspected infidelity and well-being was indirectly affected by suspicion-related distress. The effects of suspected infidelity were particularly hard on those with higher beliefs in the importance of fidelity, a history of infidelity in the relationship, and higher relationship satisfaction. The findings show that the mere suspicion of a partner's infidelity can have powerful psychological, physical, and behavioral consequences in romantic relationships.